PENGARUH PEMILIHAN KAMPAS REM PADA RODA DEPAN HONDA SONIC 150R - Maulana, Aqiem; Prasetyo, Imam; Towijaya, Towijaya (Surya Teknika : Jurnal Ilmiah Teknik Mesin, 2021)
Brakes are an important element in a vehicle that serves to reduce and stop the vehicle, allow the vehicle to park in an uneven place and a tool that ensures the safety and security of the driver. One of the important components of the brake system is the brake lining. People are often confused in choosing brake pads. The purpose of this study was to determine the effect of local product brake lining grades, genuine parts, and racing on the braking distance and time and which brake lining is better to use. This test was carried out by testing the front brake braking on a flat and straight road on a Honda Sonic 150r with a brake lever pressure of 3 kg at every speed of 30km/hour, 40km/hour, 50km/hour, and 60km/hour by testing 3 times on each canvas. brakes and speed. The test results show that racing grade brake linings are the best to use.Keywords: brake pads, distance, time.